Photochemical control of reversible encapsulation - Dube, Henry; Ajami, Dariush; Rebek, Julius (Angewandte Chemie International Edition, 2010)
(Figure Presented) Remote control: Molecules can be transferred in a chemical system between capsules and bulk solution by using light and heat. The principle is based on the isomerization of azobenzene, the trans isomer of which is encapsulated, but the cis isomer is not (see picture; C gray and brown, Br mauve; O red, N blue, H white). The photochemical control can also be used to switch between different capsular assemblies. © 2010 Wiley-VCH Verlag GmbH S. Co. KGaA.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Azobenzenes; Encapsulation; Host-guest chemistry; Photoisomerization; Supramolecular chemistry